2019
DOI: 10.3389/fmicb.2019.00133
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of 3-Chlorobenzoate-Degrading Bacterium Cupriavidus necator NH9 and Reclassification of the Strains of the Genera Cupriavidus and Ralstonia Based on Phylogenetic and Whole-Genome Sequence Analyses

Abstract: Cupriavidus necator NH9, a 3-chlorobenzoate (3-CB)-degrading bacterium, was isolated from soil in Japan. In this study, the complete genome sequence of NH9 was obtained via PacBio long-read sequencing to better understand the genetic components contributing to the strain's ability to degrade aromatic compounds, including 3-CB. The genome of NH9 comprised two circular chromosomes (4.3 and 3.4 Mb) and two circular plasmids (427 and 77 kb) containing 7,290 coding sequences, 15 rRNA and 68 tRNA genes. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 73 publications
1
29
0
1
Order By: Relevance
“…In the same study, C. basilensis strain KF708 was reclassified as Cupriavidus sp. by a combination of phylogenetic analyses and whole-genome sequence analyses [13]. Genomic analysis revealed that the strain investigated in the current study was a novel Cupriavidus species.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the same study, C. basilensis strain KF708 was reclassified as Cupriavidus sp. by a combination of phylogenetic analyses and whole-genome sequence analyses [13]. Genomic analysis revealed that the strain investigated in the current study was a novel Cupriavidus species.…”
Section: Discussionmentioning
confidence: 87%
“…We performed 16S rRNA sequencing analysis to determine the reason for the discrepancy between the Vitek 2 system and Vitek MS. Cupriavidus species are known to be difficult to identify by biochemical tests, making molecular assays necessary for accurate identification of this genus [4]. [13]. In the same study, C. basilensis strain KF708 was reclassified as Cupriavidus sp.…”
Section: Discussionmentioning
confidence: 95%
“…czcC # 12 Heavy metal RND efflux outer membrane protein Cd 2+ , Co 2+ , Zn 2+ FGG12_RS19535 czcR # 12 Cobalt-zinc-cadmium resistance protein Cd 2+ , Co 2+ , Zn 2+ FGG12_RS19515 czcE # 12 CzcE family metal-binding protein Cd 2+ , Co 2+ , Zn 2+ FGG12_RS19505 czcI # 12 Cobalt-zinc-cadmium regulatory protein Cd 2+ , Co 2+ , Zn 2+ FGG12_RS19540 cadA # 12 Cadmium-translocating P-type ATPase Cd 2+ , Co 2+ , Zn 2+ FGG12_RS19635 FGG12_RS19680 cadR # 12 Cobalt-zinc-cadmium transcriptional regulatory protein Cd 2+ , Co 2+ , Zn 2+ FGG12_RS19620 merA # 12 Mercuric ion reductase Hg 2+ FGG12_RS19735 merC # 12 Mercuric transport protein Hg 2+ FGG12_RS19740 merP # 12 Periplasmic mercury (+2) binding protein Hg 2+ FGG12_RS19745 merT # 12 Mercuric transport protein Hg 2+ FGG12_RS19750 merR # 12 Mercuric resistance operon regulatory protein Hg 2+ FGG12_RS19755 arsB* 1 Arsenic transporter (efflux pump) As 3+ , As 5+ FGG12_RS00815 arsC* 1 Arsenate reductase As 5+ FGG12_RS25020 FGG12_RS00810 arsR* 1,4,6 Transcriptional regulator As FGG12_RS00835 FGG12_RS01270 FGG12_RS11920 FGG12_RS09700 arsH* 1 Organoarsenical detoxification As 3+ FGG12_RS00805 chrA 32 Chromate transport protein (RND efflux) Cr 6+ FGG12_RS28790 copC # * 1,12 Copper resistance protein Cu 2+ FGG12_RS19835 FGG12_RS03095 copD # * 1,12,16 Copper resistance protein Cu 2+ FGG12_RS19840 FGG12_RS23205 FGG12_RS03090 copG # 12 CopG family transcriptional regulator FGG12_RS19865 copQ 2,3,5 Copper resistance protein Cu 2+ FGG12_RS04775 FGG12_RS07055 FGG12_RS08045 FGG12_RS10890 copK # 12 Periplasmic Cu(I)/Cu(II)-binding protein CopK FGG12_RS19800 cusA 2,3,5,8 Cation efflux system protein Cu 2+ , Ag + FGG12_RS04660 FGG12_RS15640 FGG12_RS08075 FGG12_RS11275 cutA 13 Periplasmic divalent cation tolerance protein Cu 2+ FGG12_RS20295 cueR 12,...…”
Section: Genesmentioning
confidence: 99%
“…In the study, conflicting results were repeatedly observed for the taxonomic classification of strain PBA that was initially identified as Ralstonia sp. PBA based on 16S rRNA gene sequence (Gan et al, 2011b; Moriuchi et al, 2019).…”
mentioning
confidence: 99%
“…In light of new genomic resources, the initial taxonomic assignment of strain PBA has also been previously questioned by Kim and Gan (2017) given its closer phylogenetic affiliation to the genus Cupriavidus than to the genus Ralstonia . Unfortunately, both recent genome-based taxonomic classifications of strain PBA (Kim and Gan, 2017; Moriuchi et al, 2019) suffered from incomplete and biased taxon sampling (restricted mostly to members from the genus Ralstonia and Cupriavidus ) that can result in the misinterpretation of evolutionary relationships (Heath et al, 2008). The taxonomic affiliation of strain PBA should be inferred from a comprehensive phylogenomic analysis that includes all genera with genome availability from the family Burkholderiaceae.…”
mentioning
confidence: 99%